Sunflower development stages for phytohormones application to cause male sterility - Destro, Deonisio; Arias, Edison Rubens Arrabal; Miglioranza, Édison; de Toledo, José Francisco Ferraz; Filho, Estafano Paluszyszyn (Pesquisa Agropecuaria Brasileira, 1993)
This trial was set in Londrina, PR, Brazil, in the crop year 82/83, to study the action of ethrel and gibberellic acid as phytohormones inducing male sterility in sunflower, applying in different developing stages of the flower. The results showed a high induction of male sterility on the variety Issanka, and of little expression on the hybrid DK-180. Gibberellic acid was less efficient to cause male sterility when applied to the flowers with 0.0 to 0.5 cm in diameter. On the other hand, gibberellic acid was more efficient in inducing male esterility on the variety Issanka, when applied to flowers ranging from 0.5 to 2.0 cm. Ethrel did not present gameticide effect.